Приріст вартості підприємства на основі прийняття рішень щодо оптимізації його логістичної системи - Кривов’язюк, Ігор Володимирович; Бурбан, Олександр Вікторович (Острог : Нац. ун-т "Острозька академія", 2025)
В роботі подальшого розвитку набули теоретико-методичні засади та практичні рекомендації щодо приросту вартості підприємства на основі прийняття рішень щодо оптимізації його логістичної системи. Розкрито взаємозалежність понять «вартість підприємства» і «логістична система». Проаналізовано драйвери приросту вартості підприємства з точки зору визначення потенційного впливу на її динаміку. Узагальнено потенційні наслідки впливу логістичної системи на драйвери зростання вартості підприємства. Запропоновано комплекс рішень з оптимізації логістичної системи підприємства, що генерують позитивний ефект впливу на приріст його вартості.

The search for ways to enhance corporate value in order to improve the effectiveness of value-based management increasingly requires non-standard decision-making. One of these ways is the optimization of the enterprise’s logistics system, whose comprehensive improvement is expected to generate synergistic effects with a positive impact on both financial indicators and corporate value drivers. Accordingly, this paper advances the theoretical and methodological foundations and provides practical recommendations for increasing enterprise value through decisions aimed at optimizing its logistics system. The methodological framework of the study is based on a set of general scientific and special methods that ensure the achievement of the research objectives: logical and content analysis – to explore the interrelation between the concepts of “corporate value” and “logistics system”; generalization and specification – to analyze the drivers of value growth in terms of their potential influence on corporate dynamics; grouping – to summarize the potential consequences of the logistics system’s impact on value growth drivers; analytical and systematic – to develop a set of logistics optimization solutions that generate a positive effect on value creation; and cause-and-effect analysis – to draw final conclusions. The results of the study include the development of theoretical and methodological provisions that form the basis for further synthesis of value theory and logistics, as well as the formulation of a set of logistics solutions aimed at optimizing the enterprise’s logistics system, which, through logistics and financial metrics, generate a positive impact on its value growth. This contributes to improving the overall effectiveness of value-based management.
Enterprise value growth based on decisions on optimization of its logistics system
Keywords: вартість підприємства; вартісно-орієнтоване управління; логістична система; оптимізація логістичних рішень; підприємство